2019
DOI: 10.1186/s12943-019-1036-9
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 promote tumor proliferation of bladder cancer by accelerating pri-miR221/222 maturation in m6A-dependent manner

Abstract: Background METTL3 is known to be involved in all stages in the life cycle of RNA. It affects the tumor formation by the regulation the m6A modification in the mRNAs of critical oncogenes or tumor suppressors. In bladder cancer, METTL3 could promote the bladder cancer progression via AFF4/NF-κB/MYC signaling network by an m6A dependent manner. Recently, METTL3 was also found to affect the m6A modification in non-coding RNAs including miRNAs, lincRNAs and circRNAs. However, whether this mechanism is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
465
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(475 citation statements)
references
References 43 publications
5
465
4
1
Order By: Relevance
“…Recent studies noted that METTL3 was drastically upregulated in bladder cancer tissues and was related to tumor histological grade. Patients with high expression of METTL3 had poor prognosis and reduced survival time (28)(29)(30). Knockdown of METTL3 significantly reduced bladder cancer cell invasion, proliferation, and survival in vitro and tumorigenicity in vivo (31).…”
Section: Mettl3 In Urological Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies noted that METTL3 was drastically upregulated in bladder cancer tissues and was related to tumor histological grade. Patients with high expression of METTL3 had poor prognosis and reduced survival time (28)(29)(30). Knockdown of METTL3 significantly reduced bladder cancer cell invasion, proliferation, and survival in vitro and tumorigenicity in vivo (31).…”
Section: Mettl3 In Urological Tumorsmentioning
confidence: 99%
“…Alarcon et al found that METTL3 promotes the maturation of miRNAs by interacting with the microprocessor protein DGCR8 (2,20). Han et al found that METTL3 positively modulates pri-miR221/222 processing in an m 6 A-dependent manner by interacting with DGCR8, resulting in a reduction in the PTEN level, which ultimately results in proliferation of bladder cancer (29). Wang et al explored the function and mechanism of METTL3 and m 6 A in colistin-induced kidney injury and found that METTL3 interacts with DGCR8 and positively modulates the processing of mature miR-873-5p in an m 6 A-dependent manner (54).…”
Section: Mettl3 Modulates Mirna Processing Via Dgcr8mentioning
confidence: 99%
“…Scientists have also reported in bladder cancer that METTL3 accelerates the processing of pri-miR221/222 via recognition by DGCR8 (46). Subsequently, mature miR221/222 restrains the expression of the antioncogene PTEN and ultimately boosts tumor growth both in vitro and in vivo.…”
Section: Mettl3mentioning
confidence: 99%
“…As the critical m6A methyltransferase, the role of METTL3 in tumours is controversial. Some studies reported that METTL3 played an oncogenic role in myeloid leukaemia, liver cancer, breast cancer, glioblastoma, bladder cancer and lung cancer . Other studies indicated that METTL3 played a tumour suppressor in renal cell carcinoma and glioblastoma .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] mRNA modifications represent another layer of epigenetic regulation of gene expression, which has been termed 'RNA epigenetics' or 'epitranscriptomics'. Among these, m6A modification is the most prevalent one in eukaryotes, 6 which occurs in mammalian mRNAs, 7,8 long noncoding RNAs, 9 micro RNAs, 10,11 involving in many RNA functions such as mRNA stability, 7 splicing, 12 transport, 13 localization and translation, 8,14 primary microRNA processing 10 and RNA-protein interactions. 15 The levels of m6A modification in mRNAs were usually controlled by so-called 'reader', 'writer' and 'eraser'.…”
Section: Introductionmentioning
confidence: 99%